Navigating the School to Work Transition: The Interplay Between Emotional Intelligence and Anxiety in Fresh Graduate at Company X - Rafy Qurniawan Bayu Sudibyo; Susana Prapunoto (Universitas PGRI Yogyakarta, 2026)
The transition from academic to professional life often creates psychological pressure for fresh graduates, particularly amidst intense job competition and post-pandemic economic uncertainty. Emotional intelligence (EQ) is believed to play a crucial role in helping individuals manage anxiety during this career transition. This study aims to analyze the relationship between emotional intelligence and work-related anxiety among fresh graduates at Company X. Using a quantitative correlational design with a cross-sectional approach, this research involved 230 fresh graduates selected through purposive sampling. Data were collected using the Schutte Emotional Intelligence Scale (SEIS) and the Career Anxiety Scale (CAS), both of which have proven validity and reliability. Data analysis was conducted using Spearman's rho correlation test. The results revealed a significant negative correlation between EQ and anxiety (r = -0.437; p < 0.01), indicating that higher levels of emotional intelligence are associated with lower levels of anxiety. The majority of participants were categorized as having moderate EQ (71.7%) and moderate anxiety (53.9%). These findings confirm that emotional intelligence serves as a psychological resource that helps new graduates manage stress and uncertainty during career transitions. The practical implications suggest that organizations should integrate EQ-based interventions into orientation and training programs for new employees to enhance emotional resilience and work readiness among young workers. Keywords: emotional intelligence, fresh graduate, anxiety, career transition, work readiness